The effect of limestone dust and different doses of mycorrhizal biological fertilizer on the growth of coffee seedlings in former quarry limestone mines - Tedi Yunanto; Suparno Suparno; Kartika Alicia Syarief (Journal of Degraded and Mining Lands Management, 2023)
Reclamation (revegetation) activities must be carried out upon the completion of mining. Limestone dust can affect the physical, chemical, and biological properties of soil. To increase the growth rate of non-wood product species such as coffee, biological fertilizers of mycorrhiza are introduced to the reclamation site. The goal of this study is to examine the effects of limestone dust covering former mines and different doses of mycorrhizal biological fertilizers on the growth of coffee seedlings. The research was conducted using the Randomized Complete Block Design method. Research areas were divided into groups/blocks consisting of soil without limestone dust, dust-covered 0-2.5 cm, and dust-covered 0-5 cm. The groups were treated with the addition of 10 g, 15 g and 20 g mycorrhizal biological fertilizers with five replications each. NPK inorganic fertilizer was given every one month to all treatments. The parameters observed from the growth of coffee seedlings were plant height, Stem diameter, and number of leaves. Based on the results, limestone dust influenced soil conditions such as silt, clay, pH, organic C, bulk density, and C/N ratio. In addition, limestone dust affected the plant height and number of leaves of coffee seedlings compared to those grown in an area without dust. Differences in the amount of mycorrhizal biologic fertilizers were significant (p<0.05) and tended to increase for the parameters of height and diameter of coffee seedlings. However, the difference in the dose of mycorrhizal biological fertilizers has been shown to significantly (p<0.05) decrease the number of leaves.